2014
DOI: 10.1177/1545968314521010
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Clinically Meaningful Improvement, According to Disability Level, of Five Walking Measures After Rehabilitation in Multiple Sclerosis

Abstract: Long walking tests and patient-reported MSWS-12 were more appropriate than short walking tests in detecting clinically meaningful improvement after physical rehabilitation, particularly the MSWS-12 for moderate to severely disabled pwMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
149
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 36 publications
(58 reference statements)
17
149
5
1
Order By: Relevance
“…A 2014 publication by Baert et al [30] on the topic of clinically meaningful improvement of walking measures concluded that the most appropriate gait measures for detecting minimally important changes (MIC) were MSWS-12 and longer walks (e.g., 6 MW); the SSST was not reviewed in this paper. The authors assessed each measure and identified minimally important changes from both the patients' and therapists' perspectives.…”
Section: Discussionmentioning
confidence: 98%
“…A 2014 publication by Baert et al [30] on the topic of clinically meaningful improvement of walking measures concluded that the most appropriate gait measures for detecting minimally important changes (MIC) were MSWS-12 and longer walks (e.g., 6 MW); the SSST was not reviewed in this paper. The authors assessed each measure and identified minimally important changes from both the patients' and therapists' perspectives.…”
Section: Discussionmentioning
confidence: 98%
“…3 Strength training for people with MS can improve strength and has been shown to have an effect on mobility, quality of life, and participation. 2,4,5 Although there are a variety of measures with favorable psychometric properties available to clinicians to assess changes in mobility and participation after strength training, such as the Timed 25-Foot Walk test, the 2-and 6-Minute Walk Tests, and the Multiple Sclerosis Walking Scale, 6,7 it can be challenging to quantify changes in strength accurately and reliably in a clinical setting.…”
mentioning
confidence: 99%
“…In the arm-ergometry and bicycling groups the improvement was most pronounced, and corresponded to ~63 m and ~56 m, respectively. These average changes are well above the threshold required for a change to be regarded as clinically relevant from a patient perspective for the 6-minute walk test of 22 m. 6 Surprisingly, arm-ergometry improved walking distance, and the authors struggle to explain this improvement. However, the most likely explanations seem to be improved core stability and/ or improved arm-swinging during walking.…”
mentioning
confidence: 90%